Radiation creep effect on the form change determination of WWER-1000 reactor core baffle under longterm operation - Chirkov, O.Yu. Chirkov; Kharchenko, V.V. (Reports of the National Academy of Sciences of Ukraine, 2021)
The paper presents the results of the analysis of the irradiation creep effect on the calculated assessment of the form change in the WWER-1000 reactor core baffle under long-term operation. The modern models of radia tion-induced swelling and radiation creep are used. They consider the effect of the stressed state and accumulated irreversible strains on the processes of swelling and creep in austenite steels under the neutron irradiation and elevated temperature. The basic tenets of the calculation of the stress-strain state in the core baffle and invessel reactor barrel considering the contact interaction are stated. The calculation analysis is performed in the two-dimensional statement for a cross-section of the core baffle with the maximum (by height) damaging dose and irradiation temperature under the generalized plane strain conditions. The data on a form change in the core baffle are obtained using the solution to the mixed contact task depending on the accumulated damaging irradiation dose. The determination of the temperature field and stress-strain state was made considering the temperature redistribution due to the violation of the design conditions of the heat carrier flow within the contact zone between the core baffle and barrel. The calculation results are determined using the median parameters of the temperature-dose dependence of the free swelling in 08Kh18N10T austenite steel. It is shown that the consideration of the radiation creep facilitates the stress level reduction, however, it increases the swelling and displacement that makes the prediction assessment of the core baffle form change more conservative as compared with the data without considering the radiation creep.